Effect of phosphorus applied as monoammonium phosphate-coated polymers in corn culture under no-tillage system - Lino, Ana Carolina Marostica [UNESP]; Buzetti, Salatiér [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Galindo, Fernando Shintate [UNESP]; Maestrelo, Paulo Ricardo [UNESP]; De Carvalho Rodrigues, Mateus Augusto [UNESP] (Universidade Estadual de Londrina, 2018)
The use of phosphate fertilizers as coated polymers reduces phosphorus losses that occur by adsorption of P to soil particles, thereby providing this essential nutrient for a longer period. The objective of this study was to evaluate the effect of phosphorus doses applied as conventional monoammonium phosphate or as coated polymers on corn grown in a clayey Oxisol, in the Cerrado region. The experiment was conducted in Selvíria – MS, located at 22°22 S and 51°22 W. The experiment was laid out in a randomized block design arranged as a 4 × 2 factorial, with four doses of P2O5 (0, 50, 100, and 150 kg ha-1) and two sources of phosphorus (monoammonium phosphate (MAP) and monoammonium phosphate coated polymers). The experiment was conducted under no-tillage system during the cropping seasons in 2008/09 and 2009/10. The MAP and MAP-coated sources did not differ in most of the yield components in either of the two seasons. We found a quadratic function adjustment for P doses up to 117 and 98 kg ha-1 of P2O5 for P concentration in leaf tissue and grain yield in the 2008/2009 crop, respectively. We also obtained a quadratic function adjustment for P rates for grain yield and number of plants, up to 118 and 113 kg ha-1 of P2O5, respectively, in the 2009/2010 harvest.
Keywords: Enhanced efficiency fertilizer; Phosphate fertilizer; Zea mays L